(untitled) (Journal of Management and Educational Sciences, 2025)
This study aims to examine master’s theses on mathematics problem-solving skills in primary schools prepared in Turkey between 2012 and 2022. A total of 25 theses related to the subject were identified between 2012 and 2022. The document review method, one of the qualitative research methods, was used to examine the theses. The study group consists of master’s and doctoral theses published nationally, which were identified by searching the YÖK National Thesis Center database using keywords such as “problem-solving skills, mathematics, elementary school” between 2012 and 2022. The introduction and theoretical background section of the study includes general explanations and definitions related to problem-solving skills. In the findings section of the research, the theses were analyzed according to the sub-objectives of the thesis, the year and type of thesis, the research method, model, data collection tools, and data analysis methods used in the theses, the province, grade level, and size of the working groups of the theses, and the subject headings and results of the theses. The final section includes the discussion, conclusions, and recommendations.